Assembly of Fluorinated Quaternary Stereogenic Centers through Catalytic Enantioselective Detrifluoroacetylative Aldol Reactions1. Issue 20 (24th March 2015) - Xie, Chen; Wu, Lingmin; Han, Jianlin; Soloshonok, Vadim A.; Pan, Yi
Abstract A Cu‐catalyzed asymmetric detrifluoroacetylative aldol addition reaction of 2‐fluoro‐1, 3‐diketones/hydrates to aldehydes in the presence of base and chiral bidentate ligand was developed. The reaction was carried out under convenient conditions and tolerated a wide range of substrates, resulting in fluorinated quaternary stereogenic α‐fluoro‐β‐hydroxy ketone products with good chemical yields, diastereo‐ and enantioselectivities. This catalytic asymmetric detrifluoroacetylative aldol addition reaction provides a new approach for the preparation of biologically relevant products containing CF quaternary stereogenic centers.